Analisis Ketersediaan Fasilitas Sosial di Kabupaten Banjarnegara, sebagai Pendukung Kondisi Darurat Bencana dan Pengembangan Wilayah - Sadali, Mohammad Isnaini; Intizhar, Fikri; Aisyah, Aisyah (Media Komunikasi Geografi, 2017)
The availability of social facilities in a region needs to be adjusted to the standard needs of regional public facilities to serve the needs of the population. Evaluation of the availability and needs of social facilities is important to support regional development. Besides that, social facilities can be an emergency infrastructure facility when disaster strikes. The existence of schools, health facilities, means of worship, a building or meeting hall becomes very important when a disaster occurs and requires rapid, appropriate, and emergency evacuation. The preparation of public infrastructure for emergency response service is one of the quick response of evacuation and anticipation of disaster victims. The results of this study are the analysis of the social facilities availability and social facilities needs as a means of public infrastructure in Banjarnegara Regency based on Indonesian National Standard. By using the analysis of serviceability, it can be evaluated the availability and needs of social facilities based on the region and can be included in regional development planning.